On reference star recognition and identification - Zariņš, Ansis; Janpaule, Inese; Kaminskis, Jānis (Geodesy and Cartography, 2014)
The paper deals with a research in the area of automation of positional star observations. In order to fully employ recent progress in imaging technologies, star image recognition and reference star identification process should gain comparable level of automation. A software package for this purpose has been developed in the Institute of Geodesy of the University of Latvia. It is capable of near-real-time image processing, star identification and astrometric position determination.